Formulasi Krim Clindamycin Sebagai Anti Jerawat dan Uji Efektivitas terhadap Bakteri Propionibacterium Acne - Doddy Rusli (Faculty of Mathtmatics and Natural Sciences, 2017)
A Research has been done by using clindamycin antibiotics as active substances against Propioni-bacterium acne bacteria. In this study clindamycin was formulated into an anti-acne cream preparation using variations of TEA emulgator concentration and stearic acid ie F1 (2%: 6%), F2 (3: 12%), F3 (4%: 18%). Then evaluated characteristics of physical quality of cream include organoleptic, homogeneity, pH, freeze thaw, vis-cosity. On the 1st day, pH, homogeneity, washability and viscosity of cream preparations were tested and freeze thaw was tested for 6 cycles for 24 days. Obtained pH and viscosity data from cream preparations. In this study F2 showed the most stable cream preparation with concentration variation (3%: 12%). The results of the analysis on the change of cream pH of F1 and F3 showed a significant change, while in F2 did not change significantly, and on the measurement of viscosity analyzed by one way anova obtained F2 is the most stable or no significant change. To test the antibacterial activity was done by diffusion method by means of wells. The result of bacteria testing with 3 repetitions showed that clindamycin cream formulation data had a larger inhi-bitory zone compared with positive control circulating in the market, with the average obtained F2: 33,76mm, F2: 32,90mm and F2: 32 , 20mm, while for the average positive control is 24,80 mm, while the negative con-trol does not show antibacterial activity. This shows that clindamycin cream has antibacterial activity.